Sistem Informasi Penerimaan Karyawan (E-Recruitment) Menggunakan Pendekatan Human Centered Design (HCD) - Rahmayan, Mentari Tri Indah; Jayanti, Endah Dwi (Jurnal Teknik Industri Terintegrasi (JUTIN), 2023)
A Web-Based Employee Recruitment Information System or e-Recruitment can be used as a solution in handling the employee recruitment process in a company. With a web-based employee recruitment information system or e-recruitment, companies can choose the right employees for their company themselves. Apart from that, companies can also process applicant data in a database so that applicant data does not accumulate in the filing cabinet. In this research, the author discusses how to design a web-based employee recruitment information system. The system development methodology used is Human Centered Design. The system was built using the PHP programming language, database server with MySQL. The result to be achieved from this research is that the web-based employee recruitment information system is expected to be able to assist the company's HRD department in the employee recruitment process and make it easier for managers to view employee recruitment reports.